Analisis Sentimen Masyarakat Indonesia Terhadap Aplikasi Threads di Twitter Menggunakan Naïve Baiyes - Fredrick Lim; Afifah Trista Ayunda (Program Studi Sistem Informasi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Raden Fatah Palembang, 2023)
Threads, a new application released by Meta in mid-2023, has sparked discussions across various social media platforms. This application has been widely compared to Twitter. This research aims to analyze the sentiment of Indonesian society regarding the emergence of Threads on social media. Various opinions were collected from Twitter posts and analyzed using the Naïve Bayes algorithm in RapidMiner to classify each public response. The results show that 28.8% of respondents view the introduction of Threads positively, while 71.2% express negative sentiment. Therefore, Threads should improve its application by adding additional features to gain broader acceptance among users. Although this research has not validated using other algorithms, it provides a general overview of the public's response to the newly emerging Threads application.